1992
DOI: 10.1111/j.1574-6968.1992.tb05474.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two gene regions involved in the expression of the imipenem-specific, outer membrane porin protein OprD ofPseudomonas aeruginosa

Abstract: A Tn501 mutant of Pseudomonas aeruginosa resistant to imipenem and lacking the imipenemspecific outer membrane porin protein OprD was isolated. The mutation could be complemented to imipenem susceptibility and OprD‐sufficiency by a cloned 6‐kb EcoRI‐PstI fragment of DNA from the region of chromosome of the wild‐type strain surrounding the site of Tn501 insertion. However, this fragment did not contain the oprD structural gene as judged by its inability to hybridize with an oligonucleotide corresponding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Future studies should be done to make effective combinations of the previously mentioned antibiotics to accelerate the recovery and shorten the duration of the illness period. To detect the imipenem heteroresistant strains, they used the double disk synergy test and SYBGreen RT-PCR for ef lux pump (Huang et al, 1992;Pirnay et al, 2002), in their study, they con irmed twenty imipenem heteroresistant strains and demonstrated that the imipenem resistant mechanism of P.aeruginosa is compromised with the high MexAB expression of ef lux pump, P.aeruginosa can go away from the bacterial membrane and resistance occur (Huang et al, 1992;Pirnay et al, 2002). They made PCR to detect the metallo β-lactamases, but not detected in the twenty heteroresistant ones.…”
Section: The Antimicrobial Susceptibility Testing Using the Kb Methodsmentioning
confidence: 99%
“…Future studies should be done to make effective combinations of the previously mentioned antibiotics to accelerate the recovery and shorten the duration of the illness period. To detect the imipenem heteroresistant strains, they used the double disk synergy test and SYBGreen RT-PCR for ef lux pump (Huang et al, 1992;Pirnay et al, 2002), in their study, they con irmed twenty imipenem heteroresistant strains and demonstrated that the imipenem resistant mechanism of P.aeruginosa is compromised with the high MexAB expression of ef lux pump, P.aeruginosa can go away from the bacterial membrane and resistance occur (Huang et al, 1992;Pirnay et al, 2002). They made PCR to detect the metallo β-lactamases, but not detected in the twenty heteroresistant ones.…”
Section: The Antimicrobial Susceptibility Testing Using the Kb Methodsmentioning
confidence: 99%
“…This unique structural feature is reflected in its channel function that protein D2 forms a channel of about 400 pico Siemens in 1 M NaC1 as reconstituted in lipid bilayers and flickers frequently [4]. The amino acid sequence deduced from the nucleotide sequence of the cloned oprD gene showed typical features of the porin proteins [5,6]. Furthermore, clinical and laboratory isolates of P. aeruginosa resistant to imipenem, one of the 13-lactam antibiotics, were found to lack protein D2 exclusively [7 9].…”
Section: Introductionmentioning
confidence: 99%